Commuting, externalities, and the geographical sizes of metropolitan areas - Eckhardt Bode (Kiel Institute for the World Economy (IfW), 2006)
The paper proposes an econometric approach for quantifying jointly the geographical scope of commuting as well as the various forms of agglomeration economies originating from metropolitan centers. Adopting an urban economics perspective, and using land prices to measure their aggregate effects, the approach estimates the geographical reach of commuting and urban externalities from a hierarchical system of gradient functions. The results for West German NUTS3 regions indicate that metropolitan areas may be larger than suggested by MSA classifications based on commuting only. Metropolitan subcenters are found to enlarge metropolitan areas significantly.
Keywords: R14; C21; C52; 330; Commuting; Agglomeration economies; Land price gradient; Urban fringe; Germany; Urban economics; Berufsverkehr; Großstadt; Ballungsraum; Agglomerationseffekt; Bodenpreis; Stadtgröße; Schätzung; Theorie; Deutschland